Residual Stress Analysis on Welded Joints by Means of Numerical Simulation and Experiments - Filippo Berto; Paolo Ferro (IntechOpen, 2018)
The ability to quantify residual stresses induced by welding processes through experimentation or numerical simulation has become, today more than ever, of strategic importance in the context of their application to advanced design. This is an ongoing challenge that commenced many years ago. Recent design criteria endeavour to quantify the effect of residual stresses on fatigue strength of welded joints to allow a more efficient use of materials and a greater reliability of welded structures. The aim of the present book is contributing to these aspects of design through a collection of case-studies that illustrate both standard and advanced experimental and numerical methodologies used to assess the residual stress field in welded joints. The work is intended to be of assistance to designers, industrial engineers and academics who want to deepen their knowledge of this challenging topic.
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Mechanical Engineering; Manufacturing Engineering